BIB-R: Uma Nova Adaptação do BitTorrent para Streaming de Vídeo sob Demanda ante Clientes Interativos em MANETs - Rodrigues, Carlo; Rocha, Vladimir (Anais do Workshop em Desempenho de Sistemas Computacionais e de Comunicação (WPerformance); 2020: Anais do XIX Workshop em Desempenho de Sistemas Computacionais e de Comunicação, 2020)
This article proposes a new adaptation of BitTorrent for video-on-demand streaming in MANETs with interactive clients. As the main innovative aspects, this proposal makes use of broadcast traffic and assesses the length of the routes, in number of hops, to be used to disseminate the video. Through simulations and evaluating different metrics, the proposed adaptation is validated and its performance is satisfactorily proven. For instance, compared to recent proposals in the literature, the final results attest to optimizations of up to 51% and 89% at the video-retrieval rate and at the display discontinuity time, respectively, which confirms adequate levels of system QoS and client QoE.